Pengenalan Web Server Pada Pelajar di Lingkungan RT01/RW14 Kelurahan Kelapa Dua Tangerang - Indra Bakti; Mohamad Firdaus (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Community Service Activities (Abdimas) aim to improve students' knowledge and skills in the RT01/RW14 environment, Kelapa Dua Village, Tangerang, in the field of information technology, especially the introduction of web servers. In this activity, students are given a basic understanding of the concept of web servers, their functions, as well as the steps in installing and configuring a simple web server. The methods used include lectures, demonstrations, and hands-on practice. The results of this activity show that students are able to understand the basic concept of web servers and apply them in the form of a simple website. This activity is expected to increase interest and ability in information technology among students, as well as provide a solid foundation for further skill development in the future.